2022
DOI: 10.1111/ped.15162
|View full text |Cite
|
Sign up to set email alerts
|

Delayed diagnosis of Kawasaki disease in Malaysia: Who is at risk and what is the outcome

Abstract: Background Data on the delayed diagnosis of (KD) is limited. This study aimed to determine the prevalence and trend of delayed diagnosis over time and identify the associated risk factors in Malaysia. Methods This retrospective, observational, population‐based study involved all children with KD registered in Johor Kawasaki Clinical Registry over 10 years (January 2010 and December 2019). The prevalence of delayed diagnosis and its trend over time was calculated. Multivariable binary logistic regression was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A recent study reported on the epidemiology and independent risk factors for delayed diagnosis of KD, which found that delayed diagnosis occurs in one in ten KD cases initially, but has gradually decreased to 4.6% over time. Children older than 1 year, with atypical clinical presentation and incomplete KD were associated with late diagnosis, while delayed diagnosis was strongly associated with the occurrence of CAL 25 . Pediatricians need accurate diagnosis of KD and timely treatment of KD in order to reduce the incidence of CAL.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study reported on the epidemiology and independent risk factors for delayed diagnosis of KD, which found that delayed diagnosis occurs in one in ten KD cases initially, but has gradually decreased to 4.6% over time. Children older than 1 year, with atypical clinical presentation and incomplete KD were associated with late diagnosis, while delayed diagnosis was strongly associated with the occurrence of CAL 25 . Pediatricians need accurate diagnosis of KD and timely treatment of KD in order to reduce the incidence of CAL.…”
Section: Discussionmentioning
confidence: 96%
“…Diagnosing KD in those who presented with atypical presentations of KD remains a challenge for physicians. Undeniably, one of the reasons for delayed diagnosis of KD is due to the atypical presentations [26]. Investigations, discussion with experts, and review of published guideline are mandatory to confirm or exclude the diagnosis of KD [27].…”
Section: Discussionmentioning
confidence: 99%